Placental thickness and its correlation with estimated foetal weight: a cross-sectional study in a tertiary care centre in South India - S. J., Goldy; Rosatte Victor, Sheba; Oral J., Bewin; Thangam, Adaline; Christopher, Usha; Rose, Adlin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The placenta is a multifaceted organ which modulates and modifies the maternal environment resulting in foetal development. It could be assumed that a healthy placenta culminates in a healthy foetus. Hence the morphometric analysis of a placenta during sonogram is inevitable. The aim of the study was to estimate the relationship between placental thickness and estimated foetal weight. Methods: The study was a cross-sectional study and included 450 antenatal women attending the department of Obstetrics and Gynaecology, Tirunelveli Medical College from May 2013 to May 2014. These women had regular cycles with a known Last menstrual period and a singleton foetus. After ethics committee approval, meticulous history including age, parity, demographic factors and past history were recorded. After obtaining consent, these women underwent placental thickness measurement between 14-40 weeks of pregnancy. Results: In the study mean placental thickness between the ranges of 11-49mm was 28.7mm and mean estimated foetal weight was 1.421kilogram. The correlation between the two was 0.943. Hence the positive correlation between the placental thickness and foetal weight is confirmed (p value <0.001). Conclusions: Determining the estimated foetal weight is an important reason for doing a sonogram, especially in third trimester. Placental thickness measured at the level of umbilical cord insertion can serve as an additional parameter in estimating foetal weight in addition to the foetal parameters, since there is a linear correlation between placental thickness and foetal weight.